Analytical Prediction of Iron Loss in a Short-stroke, Single-phase,Tubular Permanent Magnet Machine - Wang, Jiabin; Ibrahim, Taib; Howe, Dave (2009)
This paper describes an analytical method for predicting iron-loss in a short-stroke, single phase, tubular permanent magnet machine which is developed for direct-drive linear compressors in domestic refrigeration applications. The technique is based on the analytical derived magnetic filed distributions in three discrete regions of the stator core and a well established iron loss model. Finite element analysis has validated the analytical method.